Sensitivity of river ecological baseflow to climate change in arid areas - Hu, Keke; He, Jiancun; Danierhan, Sulitan; Tuerxun, Yiliyasi (Frontiers in Environmental Science, 2023)
River ecological baseflow is key to river ecosystem health and stability and has become particularly important with global climate change aggravation. By considering the Niya River Basin in Xinjiang, based on meteorological data from 1958 to 2021 and hydrological data from 1978 to 2018, the Tennant method was determined to be the best basin ecological baseflow calculation method, the M–K test was used to analyze the abrupt ecological baseflow and climate change characteristics, and the ecological baseflow regression response and sensitivity coefficient models concerning climate change were established. The results showed that 75% of the ecological baseflow in the Niya River Basin ranged from 15 to 31 m3•s−1 in 1978–2018, the average annual temperature increased by 1.6°C at a 0.22°C•(10a)−1 rate, and the annual precipitation increased by 6.3 mm at a 0.98 mm•(10a)−1 rate. The prediction accuracy of the regression model was good, R2 exceeded 0.7, the ecological baseflow response to climate change lagged, and precipitation greatly impacted ecological baseflow. The basin sensitivity coefficient showed a decreasing trend from upstream to downstream, with the annual maximum value in 2010, the minimum value in 1984, the monthly maximum value in April and the monthly minimum value in November. Based on the climate change trend and the social water use of the basin, the ecological baseflow protection targets and measures were proposed according to the season and the hydrological period for actual water resource management and scheduling of the river in this and similar regions.